Pengaruh Aplikasi Perendaman Berbagai Jenis Media Tanam dengan Beberapa Pupuk Cair Terhadap Kualitas dan Tingkat Kesukaan Konsumen Microgreen Wheatgrass (Triticum aestivum L) - Indah Maulidiyah; Mahayu Woro Lestari; Siti Asmaniyah Mardiyani (Folium : Jurnal Ilmu Pertanian, 2022)
Wheatgrass microgreen is commonly ingested as juice, which is high in vitamins, minerals, enzymes, and chlorophyll. The purpose of this study was to see how different liquid fertilizers affected the growth and quality, of wheatgrass microgreen when planted in different types of planting media., The Factorial Randomized Block Design was used in this study, with two factors: fertilizer treatment factor (P1 = Eco Enzyme 15ml/1L, P2 =Liquid Organic Fertilizer 10ml/1L, and P3 = AB mix 800ppm, and planting media factor M1 = cocopiet, M2 = rockwool, and M3 = nonwoven fabric. The results showed that the combination of planting media and liquid fertilizer had a significant effect on the amount of chlorophyll in microgreen wheatgrass, the combination of cocopeat and eco-enzyme growing media produced microgreen wheatgrass with the highest chlorophyll content(28,3). The combination of cocopeat and eco-enzyme treatment resulted the cleanest media without any fungal or bacterial contamination. Consumers' level of preference test for juice with AB mix treatment is more favored by consumers. In general, the results of this study indicate that microgreen wheatgrass grown on cocopeat and eco-enzyme media has the best combination of treatments, so it is prospective to be developed as a model of microgreen cultivation technology that is rich in chlorophyll content and is free from fungi and is potential as a raw material for natural healthy drinks rich in nutrients.